Designing a novel functional-structural NiTi/hydroxyapatite composite with enhanced mechanical properties and high bioactivity. (May 2017) - Zhang, L.; He, Z.Y.; Tan, J.; Zhang, Y.Q.; Stoica, M.; Calin, M.; Prashanth, K.G.; Cordill, M.J.; Jiang, Y.H.; Zhou, R.; Eckert, J.
Abstract: Clinical applications require porous biomaterials, however, higher porosity levels and hydroxyapatite (HA) content hampers the mechanical properties like superelasticity. Here, a functional-structural composite consisting of a central NiTi shape memory alloy core with an outer macro-porous NiTi/HA layer was fabricated by spark plasma sintering (SPS). The central NiTi alloy provides desirable mechanical properties like high strength and superelasticity, while the outer layer with controllable pore size and bioactive HA, which strongly boosts the bioactivity. This work might provide a strategy for designing and fabricating multifunctional biocompatible materials that could be promising for bone implants. Highlights: A method of rapid fabricating function-structure-integrated NiTi/HA was introduced. The central NiTi alloy provides desirable mechanical properties. The outer layer with controllable pore size and bioactive HA boosts bioactivity.